Photocatalytic formation of carbon–sulfur bonds - Wimmer, Alexander; König, Burkhard (Beilstein Journal of Organic Chemistry, 2018)
This review summarizes recent developments in photocatalyzed carbon–sulfur bond formation. General concepts, synthetic strategies and the substrate scope of reactions yielding thiols, disulfides, sulfoxides, sulfones and other organosulfur compounds are discussed together with the proposed mechanistic pathways.
Keywords: disulfides; photocatalysis; sulfones; sulfoxides; thiols; visible light